Relationship Between Proof Schemes Used by Preservice Mathematics Teachers and Gender, Views Towards Proof - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2014)
The aim of this study is to examine whether there is a relationship between gender and proof schemes used by first and final year preservice teachers attending primary and secondary education mathematics teaching program of a state university in 2011-2012 and also to investigate their general views towards proof. The study was carried out on a total of 98 preservice mathematics teachers. In order to describe current situation screening model was used. Students were asked to solve 9 problems and which proof schemes were belonged to their answers were determined. So as to set down proof schemes classification which was constituted by Harel and Sowder (1998) was used. According to the gender regarding proof schemes used by preservice teachers in the justification process of problems t table was created. Preservice teachers were interviewed so as to determine their views on proving 4 open ended questions were asked. Conversational data was given in the form of examples and in general terms. According to the results of analysis as significant differences was detected by gender in the use of some of schemes, some was concluded that the difference was not significant. Suggestions have been made on the basis of the data obtained at the end of the research. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Preservice Mathematics Teachers; Proof; Proof Schemes; Gender